Dynamics of shoot and root growth and adaptation to the environment of sainfoin (Onobrychis viciaefolia Scop.) in a hilly area of southern Italy - Pardo A.; De Falco E.; De Franchi A.S. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
Relation between aboveground and belowground growth of perennial forage crops are affected by ontogenesis and the environment in a more complex way than in other annual herbaceous crops. The purpose of this research is to evaluate the biological behaviour and adaptation to the environment of two sainfoin cultivars (ecotype 'Firenzuola' and variety 'Fakir') in a hilly area of southern Italy. At five phenological stages of the biological cycle, stem length, leaf area index and dry matter of stems, leaves, racemes, seeds, and taproot, were determined. At the end of cycle, the maximum diameter of taproot was measured. The allometric relations of the two cultivars exhibited a different behaviour. Cultivar Fakir showed, at seed ripeness, an increase of taproot mass. This could increase the amount of metabolic energy available for regrowth and ultimately affect its persistence.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)